Balance, Falls-Related Self-Efficacy, and Psychological Factors amongst Older Women with Chronic Low Back Pain: A Preliminary Case-Control Study. (9th August 2012) - Champagne, Annick; Prince, François; Bouffard, Vicky; Lafond, Danik
Abstract : Objective . To investigate balance functions in older women and evaluate the association of the fear-avoidance beliefs model (FABM) factors with balance and mobility performance. Participants . Fifteen older women with CLBP was compared with age-matched pain-free controls (n = 15 ). Main Outcome Measures . Pain intensity, falls-related self-efficacy and intrinsic constructs in the FABM were evaluated. Postural steadiness (centre of pressure (COP)) and mobility functions were assessed. Linear relationships of FABM variables with COP and mobility score were estimated. Results . CLBP showed lower mobility score compared to controls. CLBP presented lower falls-related self-efficacy and it was associated with reduced mobility scores. FABM variables and falls-related self-efficacy were correlated with postural steadiness. Physical activity was reduced in CLBP, but no between-group difference was evident for knee extensor strength. No systematic linkages were observed between FABM variables with mobility score or postural steadiness. Conclusions . Back pain status affects balance and mobility functions in older women. Falls-related self-efficacy is lower in CLBP and is associated with reduced mobility. Disuse syndrome in CLBP elderly is partly supported by the results of this preliminary study.